Molecular epidemiology and antimicrobial resistance of Haemophilus influenzae in Guiyang, Guizhou, China - Zhou, Yuhong; Wang, Yu; Cheng, Jinzhi; Zhao, Xue; Liang, Yuedong; Wu, Jiahong (Frontiers in Public Health, 2022)
Background The widespread use of antimicrobials and Haemophilus influenzae type b (Hib) vaccine worldwide has altered the epidemiological patterns of invasive H. influenzae. Nonetheless, little is currently known on the epidemiological characteristics of H. influenzae in Guiyang, Guizhou, China. Objective To determine the serotype distribution, antimicrobial resistance and Multilocus Sequence Typing (MLST) of H. influenzae in hospitalized patients in Guiyang City. Methods A total of 196 clinical isolates from hospitalized patients were collected. Serotypes were determined according to the specific capsule gene, bexA, amplified by PCR. According to the guidelines of Clinical and Laboratory Standards Institute (CLSI) 2020 drug susceptibility tested, and the results determined. The chromogenic cephalosporin nitrocefin method was used to detect β-lactamase production, β-lactamase negative, ampicillin-resistant (BLNAR) strains were detected by PCR amplification and sequencing of the penicillin-binding protein 3 (PBP3) locus of ftsI. Multilocus Sequence Typing was performed for molecular typing. Results All isolates studied were non-typeable H. influenzae (NTHi). Most patients originated from the pediatrics department (78.6%, 154/196), and suffered from lung with respiratory tract infection (pneumonia and bronchitis, 68.4%, 134/196). The resistance rates of ampicillin, cefaclor and azithromycin were 71.4% (140/196), 36.7% (72/196) and 34.2% (67/196), respectively. 40.3% (79/196) of strains were β-lactamase positive ampicillin-resistant (BLPAR). All BLPAR carried the TEM-1 gene. 9.2% (18/196) were β-lactamase negative ampicillin-resistant strains (BLNAR). The PBP3 mutation was detected in the ampicillin-resistant strains (n = 113), of which 18 belonged to group IIa. A total of 49 sequence types (ST) and 23 clonal complexes (CC) were detected, among which CC107 (ST107, n = 27; ST1002, n = 5; ST1218, n = 5) was the most frequent clonal complexes. BLPAR isolates mostly belonged to ST107 (20/79), while BLNAR was predominantly distributed in ST12 (5/18). Conclusion H. influenzae infections are predominately caused by genetically diverse NTHi among hospitalized patients in Guiyang. The prevalence of β-lactamase production and PBP3 mutation may contribute to the high local ampicillin resistance rate.